(3JbQjQ GdbhGfjf GdeJOGhdI ef Yde GdefGXQIs - (3GdeQYTj, SGLbdj RGOg, eMeO Hf CHi HcQ, J(B1145(3g`s ((3eUWai Hf Ndjds)
(3ChdgG (B:s
(3HSe Gddg hHMeOg gPG JbQjQ cJHJg JNdUG Yf GbJQGM HYV GdWdHI hdjchf dge ebOeI dWdH aQhYgG GdfGOQI , hYde GdefGXQI bhGfjf jYQa HgG CMhGd GdCHMGK GdLRFjI s
(3BNQgG (B:s
(3aGYde Cf GdbjGS eQcH cbhdfG aj EKHGJ GdYGde Cf GdYGnde dg eDKQ dCf cd eJZjQ MGOK heYQaI GdeWhjGJ JMJGL Edi HSW hdjcf gPG BNQ GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\60s
(3EjVGM Gdecfhf (B1/315s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs